A STUDY OF MEDAN HELVETIA SUB DISTRICT MORPHOLOGICAL PATTERNS WITH URBAN DESIGN THEORY APPROACH - Nasution, Fitri Rahmawati (Talenta Publisher, 2022)
This study aims to determine and understand the current morphological patterns of Medan Helvetia Sub District. It is due to the need for reconsideration regarding the spatial structure of the sub-district because there are several problems troubling residents, namely frequent congestion and flooding. By using a descriptive methodology, this research uses several methods, starting with secondary data collection. Secondary data obtained shows that the study of Medan Helvetia Sub District morphological patterns is using the urban design theory approach, which is composed of three aspects, namely figure-ground, linkage, and place. The next method is discussing the data that has been obtained and ending with finding answers to research problems. The findings are useful as references in developing the physical design of this sub-district in the future. Keywords: figure-ground, linkage, Medan Helvetia Sub District, morphological patterns, place